Effects of Delayed Hip Fracture Surgery on Mortality and Morbidity in Elderly Patients - Rodriguez-Fernandez, Pedro (Springer-Verlag, 2011)
BACKGROUND: The effects of delaying hip fracture surgery on mortality and morbidity in elderly patients are not completely understood. QUESTIONS/PURPOSES: We examined the effects of delays in surgical treatment of hip fracture on mortality, postoperative complications, length of stay in hospital, and functional recovery, in elderly patients. PATIENTS AND METHODS: We studied two groups of patients with hip fractures. The first group was studied retrospectively (n = 109); these patients had been exposed to an average delay in receiving surgical treatment of more than 1 week owing to a fire at our hospital. Patients in the second group (n = 79), which we studied prospectively, were operated on within 48 hours of experiencing the fracture or as soon as their medical condition permitted. Rates of mortality and complications were registered for each group. RESULTS: We found a larger number of complications in the group with a delay in surgical treatment (pressure ulcer, urinary infection, deep vein thrombosis, and postoperative length of stay), but there were no differences in mortality or functional recovery at 3 months and 1 year. CONCLUSIONS: A 1-week delay in the surgical treatment of elderly patients with hip fractures did not increase the mortality rate or prolong the period of recovery but did increase the incidence of postoperative complications. Our experience suggests elderly patients with hip fractures should be operated on as soon as their medical condition permits. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.